Knowledge, attitude and practices among mothers regarding childhood obesity at Kuantan, Malaysia - Mohd Hatta, Nur Khairul Bariyyah; A Rahman, Nor Azlina; A Rahman, Nor Iza; Haque, Mainul (Japan International Cultural Exchange Foundation, 2017)
Background: The prevalence of childhood obesity has been increasing alongside rapid global economic development including Malaysia. The aims of this study were to assess the knowledge, attitude and practices (KAP) of mothers regarding childhood obesity and to determine the factors associated with the KAP as well as to map the correlation between KAP. Methods: A cross sectional study was conducted on 100 mothers aged above 18 years attending a Mother and Child Clinic in Kuantan, Malaysia. They had to fill up the consent form and questionnaires. Results: The survey revealed that mothers had moderate KAP on childhood obesity. Twenty three to 87 mothers answered correctly on knowledge part, 4 to 54 mothers and 17 to 76 mothers answered correctly on attitude and practices respectively. The knowledge was associated with educational level (t = -4.411, p < 0.001), age (r = +0.222, p = 0.026) and income (r = +0.337, p = 0.013). While attitude was associated with educational level (t = -4.384, p < 0.001), occupation (t = +2. 082, p = 0. 040) and income (r = +0.326, p = 0.016). It indicates that as educational level and income increased, the knowledge and attitude also increased. While as age increased, knowledge also increased. Different type of mother's occupation showed a different attitude on childhood obesity. There was a correlation between attitude with knowledge (r = +0.414, p < 0.001) and practices (r = +0.261,p = 0.009) but there was no correlation between knowledge and practices (r = +0.158, p = 0.116). Conclusions: It showed that a good attitude is related to higher knowledge and best practices, but high knowledge does not mean it had good practices. These findings may be useful in targeting programs and strategies for preventing and intervention of childhood obesity.